2012
DOI: 10.1590/s0104-14282012005000022
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização viscosimétrica de nanocompósitos híbridos PS/POSS

Abstract: Resumo: Nanocompósitos híbridos de poliestireno (PS) e poliedros oligoméricos silsesquioxanos (POSS) com diferentes composições e graus de hibridização foram obtidos por processamento reativo no estado fundido utilizando-se peróxido de dicumila (DCP) como iniciador, na presença ou não de estireno como agente de transferência de radical. Os materiais foram caracterizados viscosimetricamente por cromatografia de permeação em gel (GPC) usando detecção tripla por espalhamento de luz, viscosimetria e índice de refr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…In the case of acrylic fiber production viscosity related molecular weight is used as a control method for polymer quality. Although widely used, viscosity is not an absolute method to measure molecular weight, since it depends on other properties, such as temperature, polymer morphology, size and shape of the solvent molecules [21][22][23][24] . Solution viscosity is basically a measure of the size or extension in space of polymer molecules, and is empirically related to molecular weight for linear polymers [2] .…”
Section: Determination Of Intrinsic Viscosity and The Viscometric Molmentioning
confidence: 99%
See 4 more Smart Citations
“…In the case of acrylic fiber production viscosity related molecular weight is used as a control method for polymer quality. Although widely used, viscosity is not an absolute method to measure molecular weight, since it depends on other properties, such as temperature, polymer morphology, size and shape of the solvent molecules [21][22][23][24] . Solution viscosity is basically a measure of the size or extension in space of polymer molecules, and is empirically related to molecular weight for linear polymers [2] .…”
Section: Determination Of Intrinsic Viscosity and The Viscometric Molmentioning
confidence: 99%
“…However, several studies reported that at low polymer concentration in the solution, and thus it is diluted, it makes feasible to extrapolate to infinite dilution [2,[21][22][23][24] . According to Etxabarren [23] , in most cases the concentration dependence is not relevant in applications which the polymer concentration tends to a weight or volume fraction close to unity.…”
Section: Intrinsic Viscosity and Viscosity Average Molecular Weight M Vmentioning
confidence: 99%
See 3 more Smart Citations